LACK OF STUDENT LEARNING CONCENTRATION ON CIVICS LEARNING IN CLASS I SAQU KHALIFAH AL MUNAWAWARAH ELEMENTARY SCHOOL ACEH BESAR - Raudhatul Muna; Siti Mayang Sari; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Active learning is learning that involves stimulus and response betweeneducators and students. In the learning process, learning concentrationabsolutely needs to be possessed by every student in the learning process, thisis because concentration has a big influence on student learning outcomes andthe goals of learning. Based on the facts that occurred in class 1 of SaQuKhalifah Al Munawwarah Elementary School, students' learning concentrationwas very low. The lack of concentration on students' learning in class 1 of SDSaQu Khalifah Al Munawwarah in the Civics learning process resulted in a lesseffective learning process. The aim of this research is to describe theimplementation and obstacles of students not paying attention to the teacher'sexplanations in class 1 of SD SaQu Khalifah Al Munawwarah. This researchuses a descriptive qualitative research method, namely research based on eventsthat occurred at SaQu Khalifah Al Munawwarah Elementary School, AcehBesar. Through this research method, it will be detailed clearly to create anactive learning process. The research results show that students' lack ofconcentration in learning is caused by the learning process taking place duringthe day and less active learning. So it can be concluded that the learning processthat occurs is less effective and even tends to be passive.